STUDI ETNOGRAFI TENTANG KEJADIAN STUNTING PADA SUKU BATAK TOBA DI DESA BATUBINUMBUN KECAMATAN MUARA - Dita Putri Togatorop; Afnijar Wahyu (Jurnal Riset Multidisiplin Edukasi, 2025)
Background: Stunting is a major nutritional issue both in the country and globally. It is considered a severe consequence of prolonged malnutrition. Stunting is also a condition of chronic malnutrition experienced by children aged 6-59 months, which results in lower intelligence, reduced immunity, and lower productivity in children.  Objective: To identify the characteristics of factors causing stunting among the toba batak people in batubinumbun village,muara district. Method : This research employed a qualitative method with an ethnographic design. The techniques used include observation, interviews, and documentation.Results: The study found four factors:daily consumption of like toba water,failure to utilize health services,dietary restrictions during pregnancy,lack of knowledge about maternal nutrition,and limited family income to meat children’s needs. Conclusion:several vaktors contribute to stunting among the toba batak people in batubinumbun village muara district. Suggestion : For future researchers, this study serves as a source of information and knowledge and as a reference for further research, which could be expanded by examining other variables to gather more information on preventing stunting in toddlers.